PERSPEKTIF HUKUM HAK CIPTA ATAS PENGGUNAAN MATERI CERAMAH, LAGU DAN/ATAU MUSIK DALAM PEMBUATAN VIDEO DENGAN MENGGUNAKAN APLIKASI DUBSMASH MENURUT PRINSIP FAIR USE - MUHAMMAD FADHLI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Dr. Saidin, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Jelly Leviza, SH, MHum Internet is an information technology development as new media. Dubsmashappears as mobile application to make selfie dubbing video, using popular audio;the result is distributed through social media. A problem occurs when the soundrecording is citation of a popular song or film protecting by copyright, but thereis an exception of using the work of a composer which is called, fair use principle.The research used descriptive analytic method with juridical normativeapproach. The data were analyzed qualitatively, and the conclusion was drawndeductively through normative framework.Videos result dubsmash applications has violated the moral values ofcomposers and/or copyright holders in which the users have mutilated the workart such as popular audio of other people’s music or films of other people’s sound(Article 5, paragraph 1 of UUHC). However, in the fair use principle, since it isnot commercial and for personal use and/or does not give any profit to Dubsmashusers and there is no objection from the composers (Article 43, letter d of UUHC).The video and Dubsmash distributed to social network is not protected by lawaccording to Article 7, paragraph 1, letter (a) of UUHC since there is nooriginality element in it; it is only common work which belongs tocinematography. The legal protection for composers and/or copyright holders ispreventive and repressive (Article 55 and Article 95, paragraph 1 of UUHC).It is recommended that the Government intensively inform internet users notto violate other people’s copyright. Executive and/or Legislative Institutions should explain clearly the requirements of a work of art which protected bycopyright. Those who feel harmed should report to the Dubsmash or theauthorities or bring the case to the Commercial Court for the process of litigation.Keywords: Copyright, Video, Dubsmash, Fair Use